Detection of Bioavailable Cadmium by Double-Color Fluorescence Based on a Dual-Sensing Bioreporter System - Hui, Chang-ye; Guo, Yan; Wu, Jian; Liu, Lisa; Yang, Xue-qin; Guo, Xiang; Xie, Ying; Yi, Juan (Frontiers in Microbiology, 2021)
Cadmium (Cd) is carcinogenic to humans and can accumulate in the liver, kidneys, and bones. There is widespread presence of cadmium in the environment as a consequence of anthropogenic activities. It is important to detect cadmium in the environment to prevent further exposure to humans. Previous whole-cell biosensor designs were focused on single-sensing constructs, but have had difficulty in distinguishing cadmium from other metal ions such as lead (Pb) and mercury (Hg). We developed a dual-sensing bacterial bioreporter system to detect bioavailable cadmium by employing CadC and CadR as separate metal sensory elements and eGFP and mCherry as fluorescent reporters in one genetic construct. The capability of this dual-sensing biosensor was proved to simultaneously detect bioavailable cadmium and its toxic effects using two sets of sensing systems while still maintaining similar specificity and sensitivity of respective signal-sensing biosensors. The productions of double-color fluorescence were directly proportional to the exposure concentration of cadmium, thereby serving as an effective quantitative biosensor to detect bioavailable cadmium. This novel dual-sensing biosensor was then validated to respond to Cd(II) spiked in environmental water samples. This is the first report of the development of a novel dual-sensing whole-cell biosensor for simultaneous detection of bioavailable cadmium. The application of two biosensing modules provides versatile biosensing signals and improved performance that can make a significant impact on monitoring high concentration of bioavailable Cd(II) in environmental water to reduce human exposure to the harmful effects of cadmium.